Comparison of Black Magnetic Powder and Phase Transfer Catalyst Methods to Develop Latent Fingerprints on Latex Surface: A Preliminary Study (International Journal of Scientific Research in Science and Technology, 2026)
Latent fingerprints are important pieces of physical evidence at crime scenes, playing a significant role in individualization. Such fingerprints can be detected on a variety of surfaces, including used latex gloves, which are frequently found at crime scenes. Although fingerprints on latex gloves are common, there has been limited research on identifying them accurately. The aim of this study was to create a new method for producing latent fingerprints on latex surfaces utilizing black magnetic powder and the Phase Transfer Catalyst (PTC) reagent approach, which might be useful for crime scene investigators. The research also addressed the PTC reagent’s shelf life. The research employed two fingerprint development techniques: black magnetic powder and a PTC reagent formulated from non-toxic chemicals. Over the course of seven days, latent fingerprints were developed on latex surface at various intervals. The developed prints were photographed to determine their quality. Both approaches, black magnetic powder, and the PTC reagent, were found to be successful in developing latent fingerprints on latex glove surfaces. Both approaches produced comparable-quality fingerprints, with clear prints acquired up to seven days following deposition. A number of physical and chemical processes are available for fingerprint formation, depending on the surface and type of the print. Both black magnetic powder and the PTC reagent proved effective in developing latent fingerprints on latex surfaces. The black magnetic powder technique is a useful tool since it is simple and easy to use, and also the PTC reagent is stable for at least seven days.